2017
DOI: 10.1002/cyto.a.23080
|View full text |Cite
|
Sign up to set email alerts
|

A flowcytometric analysis to efficiently quantify multiple innate immune cells and T Cell subsets in human blood

Abstract: The balance of inflammation and immunosuppression driven by changed ratios in diverse myeloid and T cell subsets, as well as their state of activation and ability to migrate to lymphoid compartments or inflammatory sites, has emerged as a highly active area of study across clinical trials of vaccines and therapies against cancer, trauma, as well as autoimmune and infectious diseases. There is a need for effective protocols which maximally use the possibilities offered by modern flow cytometers to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…After thawing, peripheral blood mononuclear cell were washed twice and transferred to a 96-well roundbottom plate (Corning, Corning, NY, USA) to be stained with a fluorochrome label. We have recently established two antibody cocktails for surface staining of peripheral blood mononuclear cells to assess the cellular innate immune response [9]. The assessed myeloid and lymphoid cell populations as well as functional markers were chosen as they represent key cells/markers involved in inflammation and immune stimulation as well as immunosuppression (see also Supporting Information, Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…After thawing, peripheral blood mononuclear cell were washed twice and transferred to a 96-well roundbottom plate (Corning, Corning, NY, USA) to be stained with a fluorochrome label. We have recently established two antibody cocktails for surface staining of peripheral blood mononuclear cells to assess the cellular innate immune response [9]. The assessed myeloid and lymphoid cell populations as well as functional markers were chosen as they represent key cells/markers involved in inflammation and immune stimulation as well as immunosuppression (see also Supporting Information, Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have shown no effect of cryopreservation in the enumeration of T cells, helper CD4+ and cytotoxic CD8+ T cells 2, 7, 8, 11, 12 . These results are largely consistent with the results of our study where we did not find any pairwise differences in percentage of total T cells unless cells were cryopreserved after a delay in cell processing for 72 hours.…”
Section: Discussionmentioning
confidence: 81%
“…Using manually defined gates, we examined the CD45 + fraction of human thymic MNC in order to identify populations of CD19 + HLA-DR + B cells, HLA-DR + CD123 + plasmacytoid dendritic cells (pDCs) and HLA-DR + CX3CR1 + conventional dendritic cell and macrophages (cDC/macro) ( Figure 2A ) and HLA-DR + CD14 + monocytes ( Figure S1A ) ( 23 , 24 ). These populations were used to assess the performance of our graph-based clustering approach, which appeared to successfully identify the distinct populations ( Figure 2B and Figure S1B ) and which recapitulated the phenotype of manually identified mature non T-lineage subsets based on both the biexponentially transformed scatterplots ( Figure 2C and Figure S1C ) and the median fluorescent indices (MFIs) of each of the annotated clusters ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%